1986
DOI: 10.1002/j.1460-2075.1986.tb04607.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anti-HIV neutralizing antibodies by synthetic peptides.

Abstract: Two synthetic peptides containing amino acid sequences analogous to the envelope glycoprotein of human T‐lymphotropic virus (HTLV) type III (HTLV‐III) and lymphadenopathy associated virus (LAV) were produced and used to immunize rabbits. The subsequent rabbit antisera neutralized HTLV‐III infectivity in vitro. The two synthetic peptides corresponded to regions associated with the gp120 or gp41 subunits respectively, of human immunodeficiency virus (HIV). This data indicates that at least two neutralizing epito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
108
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(114 citation statements)
references
References 48 publications
5
108
1
Order By: Relevance
“…It is interesting that some antibodies raised against the cytoplasmic tail of human immunodeficiency virus gp41 neutralize infection (2,15). This observation led to the suggestion that these sequences were expressed on cell surfaces, although this proposal is controversial (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that some antibodies raised against the cytoplasmic tail of human immunodeficiency virus gp41 neutralize infection (2,15). This observation led to the suggestion that these sequences were expressed on cell surfaces, although this proposal is controversial (30).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the external portion of gp4l and perhaps part of p17 have also been reported to be sensitive to neutralizing antibodies (146,222,839,1040) (see Sections XIV F and XXII A). The antibodies to p17 could indicate some protrusion of this core protein to the outside of the virion.…”
Section: Hiv Virionmentioning
confidence: 99%
“…In contradiction to this classical model, several studies have described antibodies strongly reacting with a region situated C terminally to the membrane-spanning domain, thought to be located within the cell, in serum samples of HIV-infected patients (6,10,23,30,59). Furthermore, some groups have reported that antibodies against this region are able to modestly neutralize some strains of HIV type 1 (HIV-1) and HIV-2 under modified conditions in vitro (3,9,15,19,25,35,36).…”
mentioning
confidence: 98%